Molecular mobility and relaxation process of isolated lignin studied by multifrequency calorimetric experiments - Guigo, Nathanael; Mija, Alice; Vincent, Luc; Sbirrazzuoli, Nicolas (Physical chemistry chemical physics : PCCP, 2009)
The glass transition of lignin has been studied by multifrequency calorimetric measurements in order to highlight the morphological changes and the dynamic aspects associated to this relaxation process. Influences of water sorption and thermal annealing on molecular mobility have been considered. Additional investigations by thermogravimetry, infra-red spectroscopy and rheometry have been performed to corroborate the claims. The relaxation process of annealed lignin shows a different behaviour as the consequence of micro-structural modifications of lignin. These are explained by redistribution of secondary bonds as well as formation of new interunit linkages. Concerning the dynamic aspects, apparent activation energy, E, and sizes of cooperatively rearranging region, V(crr), have been evaluated respectively from the frequency dependence and heat capacity measurements of the glass transition. Compared to dried lignin, both E and V(crr) significantly decrease in a water-sorbed matrix indicating that the three-dimensional structure presents a higher mobility and is less confined.